TAFSIR DAN TAKWIL - Hamnah Hamnah (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2020)
Al-Qur'an was revealed as a life guide for humans who will convey people to goodness in this world and the hereafter for those who follow it. Al-Qur'an also as evidence of the prophet Muhammad's apostleship. and the al-Qur'an he must convey to his people and explain the contents of his womb to all mankind. Not all of the verses of the Koran are clear in meaning to be understood by the companions when the Prophet delivered them, there are also verses of the Koran that are still vague and the Prophet had to explain their meaning in order to be understood by the companions at that time, and this lasted until the Prophet died. After the Prophet's death, the companions used their own ijtihad when interpreting the verses of the al-Qur'an which they did not understand, especially the companions who had the ability in this regard. Furthermore, they had students from tabi'in circles who would later become new figures in the field of interpretation. In the history of the development of tafsir, some have tried to interpret the verses of the Qur'an in a meaningful / substantive way, which has led to a new term in interpretation, namely takwil. There are not too many differences between tafsir and takwil and there are scholars who equate them even though there are differences. The history of interpretation continues to develop from classical to contemporary periods, and each of its developments has a different style and that pattern is adapted to the conditions of the society. Tafsir in Indonesia, the development of the interpretation of the Koran is somewhat different from that in the Arab world, which is the place where the Koran was revealed and at the same time the birthplace of the interpretation of the Koran, and these differences are caused by culture and language. Indonesia looks unique from the others because there are interpretations of the Koran according to the local language where the interpreter lives, so that interpretations of the Koran emerge that use regional languages ​​other than Indonesian.